The effect of early environment on the adaptability of chicks - Mccrea, Kirste Colleen (2021)
Due to the many challenges that laying hens face throughout their lives in the production system, raising hens with the ability to adapt and cope within their environment is vital from both a welfare and production standpoint. The early environment of chicks has been shown to have lasting effects on the health and well being of laying hens later in life. However, few studies have investigated the effects of early environment and adaptability. This study investigated cognitive functions and learning capabilities, which are pivotal in developing adaptation skills, of 48 laying hens at the age of 9-14 weeks using a holeboard test. Hens were raised in differing environments over two periods of rearing: early rearing from 0-4 weeks of age and current rearing from 5-15 weeks of age. The treatments consisted of choice of substrate and perch (four types of each) vs. no choice of substrate or perch (i.e. one type of each), which was changed between the two rearing periods for half of the birds, resulting in four different treatments i.e. choice/choice (CC), choice/no-choice (CN), no-choice/no-choice (NN), and no-choice/choice (NC). When habituating individually to the holeboard test, birds from treatment CC found more worms than those from treatments NN and CN (p=0.004; p=0.03). During acquisition, a significantly higher number of birds from CC and NC completed the start trials when compared to NN and CN birds (p=0.04). Furthermore, results from the reversal phase indicated that NC birds had a higher reference memory than NN birds. Overall these results suggest that having choice in the current rearing environment influenced the birds’ success in the holeboard test, which may in turn be directly related the their ability to adapt to new environments and circumstances. Supplementary studies into the critical stage of early rearing and when choice is best suited to be introduced may provide further insights into the role that choice plays on the adaptability of laying hens.